Study of Differences in Arabic Lahjah: Dialectal Variations in Various Arab Countries - Setiyadi, Alif Cahya; Putri, Nurmayahati Mulia; Silmy, Ahmad Nahidl (STIQ Amuntai, 2024)
Arab countries have a wide varity of dialects, which are varieties of Arabic that arise from the different ways of speaking of Arab Communities in Different regions that have different places of residence and socio-cultural needs. Arabic dialects have unique characteristics in each country, affecting daily communication and the culture of the local community. This research aims to identify Arabic dialect variations (Lahjah Arabiyah) descriptively. This research is ad descriptive qualitative based on literature study. Researchers collected data related to the variety of Arabic dialects through documentation, namely by reviewing texts from various printed books and scientific journal articles.